Frontal neurocysticercosis and attention deficit. (Colombia Medica, 2007)
Introduction: Neurocysticercosis (NCC) is the most common parasitic disease of the central nervous system. Epilepsy, pyramidal tract dysfunction, increased intracranial pressure and intellectual deterioration are the most frequently recognized clinical manifestations of NCC. Materials and methods: A total of five cases of frontal neurocysticercosis with diagnosis made by neuro-imaging studies are discussed. Symptoms as focal seizures associated to attention deficit were found. To all of them EEG, ELISA in blood and to four in LCR were carried out. Patients were treated with albendazol and carbamazepine. Methylphenidate as a pharmacologic treatment for attention deficit was also prescribed. Results: All of the patients had restlessness to the physical examination, they were impulsive and had inattention. The cerebral computed tomography detected in most of the cases injury (80%) and in one case it was necessary to make additional magnetic resonance imaging to verify it. Only in one case the electroencephalogram was abnormal, with slow temporo-occipital waves observed. CT showed frontal calcificated injuries, after medical treatment. There were no side effects to medication. Conclusion: Patients with frontal NCC may display upheavals of attention deficit and hyperactivity, that could be explained by the dysfunction frontostriatal theory, as it happens in the attention deficit and hyperactivity disorder (ADHD). In endemic zones of NCC like Colombia, it is necessary to consider this condition in children presenting symptoms of ADHD, especially in pediatric patients without any previous conduct disorder, since there are children with structural neurological upheavals with ADHD symptoms.